Neurofeminism and feminist neurosciences: a critical review of contemporary brain research - Schmitz, Sigrid; Höppner, Grit (Frontiers in Human Neuroscience, 2014)
To date, feminist approaches to neurosciences have evaluated the debates surrounding practices of knowledge production within and research results of contemporary brain research. Consequently, neurofeminist scholars have critically examined gendered impacts of neuroscientific research. Feminist neuroscientists also develop research approaches for a more gender-appropriate neuroscientific research on several levels. Based on neurofeminist critique feminist neuroscientists aim to enrich neuroscientific work by offering methodological suggestions for a more differentiated setup of categories and experimental designs, for reflective result presentations and interpretations as well as for the analysis of result validity. Reframing neuro-epistemologies by including plasticity concepts works to uncover social influences on the gendered development of the brain and of behavior. More recently, critical work on contemporary neurocultures has highlighted the entanglements of neuroscientific research within society and the implications of ‘neurofacts’ for gendered cultural symbolisms, social practices, and power relations. Not least, neurofeminism critically analyses the portrayal of neuro-knowledge in popular media. This article presents on overview on neurofeminist debates and on current approaches of feminist neurosciences. The authors conclude their review by calling for a more gender-appropriate research approach that takes into account both its situatedness and reflections on the neuroscientific agenda, but also questions neurofeminist discourse in regards to uses and misuses of its concepts.